Pengaruh Media Sosial Terhadap Pola Komunikasi dalam Keluarga Generasi Z - Sinaga, Astriana Baiti; El Adawiyah, Sa'diyah (Universitas Djuanda Bogor, 2026)
Digital communication is now embedded in everyday family life, especially for Generation Z adolescents who rely heavily on smartphones and social media. This shift raises a central concern: when messaging becomes the default, does the quality of family communication change? This study examines the influence of social media use on family communication patterns among mid-adolescent Gen Z. A quantitative survey was administered to 237 senior high school students in Jakarta (ages 15–18). The data were analyzed descriptively to map device ownership, platform preferences, and the ways social media is used in daily interaction with parents and siblings. Results show near-universal smartphone ownership and frequent social media use in everyday routines, including learning and communication at home. WhatsApp emerged as the dominant platform for family interaction, and many respondents reported choosing chat-based communication even while they were physically at home. Social media produced a double-edged effect. On the positive side, it supports fast, low-cost, distance-independent communication, helps coordinate family activities, and enables quick sharing of updates. On the negative side, heavier use was associated with reduced openness, weaker togetherness, and fewer meaningful face-to-face conversations, alongside concerns about the fading of traditional family values. Overall, the findings suggest that social media can strengthen connectivity, but direct interaction remains essential for sustaining warm and healthy family communication.